Cysteine peptidases of Eudiplozoon nipponicum: a broad repertoire of structurally assorted cathepsins L in contrast to the scarcity of cathepsins B in an invasive species of haematophagous monogenean of common carp - Jedličková, Lucie; Dvořáková, Hana; Dvořák, Jan; Kašný, Martin; Ulrychová, Lenka; Vorel, Jiří; Žárský, Vojtěch; Mikeš, Libor (Parasites & vectors, 2018)
BACKGROUND: Cysteine peptidases of clan CA, family C1 account for a major part of proteolytic activity in the haematophagous monogenean Eudiplozoon nipponicum. The full spectrum of cysteine cathepsins is, however, unknown and their particular biochemical properties, tissue localisation, and involvement in parasite-host relationships are yet to be explored. METHODS: Sequences of cathepsins L and B (EnCL and EnCB) were mined from E. nipponicum transcriptome and analysed bioinformatically. Genes encoding two EnCLs and one EnCB were cloned and recombinant proteins produced in vitro. The enzymes were purified by chromatography and their activity towards selected substrates was characterised. Antibodies and specific RNA probes were employed for localisation of the enzymes/transcripts in tissues of E. nipponicum adults. RESULTS: Transcriptomic analysis revealed a set of ten distinct transcripts that encode EnCLs. The enzymes are significantly variable in their active sites, specifically the S2 subsites responsible for interaction with substrates. Some of them display unusual structural features that resemble cathepsins B and S. Two recombinant EnCLs had different pH activity profiles against both synthetic and macromolecular substrates, and were able to hydrolyse blood proteins and collagen I. They were localised in the haematin cells of the worm's digestive tract and in gut lumen. The EnCB showed similarity with cathepsin B2 of Schistosoma mansoni. It displays molecular features typical of cathepsins B, including an occluding loop responsible for its exopeptidase activity. Although the EnCB hydrolysed haemoglobin in vitro, it was localised in the vitelline cells of the parasite and not the digestive tract. CONCLUSIONS: To our knowledge, this study represents the first complex bioinformatic and biochemical characterisation of cysteine peptidases in a monogenean. Eudiplozoon nipponicum adults express a variety of CLs, which are the most abundant peptidases in the worms. The properties and localisation of the two heterologously expressed EnCLs indicate a central role in the (partially extracellular?) digestion of host blood proteins. High variability of substrate-binding sites in the set of EnCLs suggests specific adaptation to a range of biological processes that require proteolysis. Surprisingly, a single cathepsin B is expressed by the parasite and it is not involved in digestion, but probably in vitellogenesis.
Keywords: gastrointestinální trakt; Gene Expression Profiling; rekombinantní proteiny; Cathepsin L; Gastrointestinal Tract; kapři; zavlečené druhy; proteolýza; kathepsin B; Cathepsin B; Proteolysis; Carps; zvířata; Introduced Species; Host-Parasite Interactions; Trematoda; interakce hostitele a parazita; stanovení celkové genové exprese; kathepsin L; Hydrolysis; hydrolýza; Recombinant Proteins; Animals